2015
DOI: 10.1111/1750-3841.12783
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hydrothermal‐Calcium Chloride Treatment and Chitosan on Quality Retention and Microbial Growth during Storage of Fresh‐Cut Papaya

Abstract: Rapid degradation of fresh-cut papaya limits its marketability. Hydrothermal treatments in combination with a calcium dip, applied to whole fruit before slicing, and also the application of chitosan as a coating film, have been found to have very good results in maintaining the quality of fresh-cut fruits. Based on these considerations, the aim of this study was to evaluate the effect of hydrothermal treatment (HT; 49 °C, 25 min) containing calcium chloride (Ca; 1%, w/v) followed by dipping in chitosan (Chit; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Additionally, the combined treatment of hot water and calcium applied on fruits has resulted better than any individual treatment to maintain the postharvest quality and to reduce storage disorders (Shahkoomahally & Ramezanian, ; Sharma, Singh, & Pal, ). In this regard, our previous results showed that the hot water immersion treatment combined with calcium chloride delays the anthracnose development in papaya inoculated with Colletotrichum gloeosporioides during 20 days of storage at 12°C (Ayón‐Reyna, López‐Valenzuela et al, ; ) and induces changes in bioactive compounds of whole and fresh‐cut papaya (Ayón‐Reyna et al, ; ; Ayón‐Reyna, López‐Valenzuela et al, ; ). Moreover, this combined treatment improves the antioxidant activity and profile of bioactive compounds in whole and fresh‐cut apple (Aguayo, Requejo‐Jackman, Stanley, & Woolf, ; Sharma, Singh, & Pal, ) and kiwifruit (Shahkoomahally & Ramezanian, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the combined treatment of hot water and calcium applied on fruits has resulted better than any individual treatment to maintain the postharvest quality and to reduce storage disorders (Shahkoomahally & Ramezanian, ; Sharma, Singh, & Pal, ). In this regard, our previous results showed that the hot water immersion treatment combined with calcium chloride delays the anthracnose development in papaya inoculated with Colletotrichum gloeosporioides during 20 days of storage at 12°C (Ayón‐Reyna, López‐Valenzuela et al, ; ) and induces changes in bioactive compounds of whole and fresh‐cut papaya (Ayón‐Reyna et al, ; ; Ayón‐Reyna, López‐Valenzuela et al, ; ). Moreover, this combined treatment improves the antioxidant activity and profile of bioactive compounds in whole and fresh‐cut apple (Aguayo, Requejo‐Jackman, Stanley, & Woolf, ; Sharma, Singh, & Pal, ) and kiwifruit (Shahkoomahally & Ramezanian, ).…”
Section: Introductionmentioning
confidence: 98%
“…(Sharma, ). The bioactive compounds of papaya fruit can reduce the risk of degenerative diseases such as cancer, diabetes, and cardiovascular diseases (Ayón‐Reyna et al, ; Moo‐Huchin et al, ). However, papaya fruit is highly perishable after harvest and shows accelerated softening during the maturation process that is associated with high susceptibility to fungal pathogens (Sharma, ).…”
Section: Introductionmentioning
confidence: 99%
“…On days 3, 7, and 10 of storage at 25 °C, CaO[W]‐GSE/CW[C] mandarins showed significantly higher ascorbic acid concentrations than untreated and GSE/CW[C] mandarins ( P < 0.05). This indicated that GSE/CW coating after washing with CaO was helpful in delaying the decrease in ascorbic acid concentration in mandarins, which may be due to the regulation of ascorbic acid oxidation by calcium ions (Ayón‐Reyna et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…As a texture indicator, firmness of broccoli florets was measured using a digital penetrometer (Chatillon DFE 100, Ametek TCI division, Largo, Fl., U.S.A.) with an 11‐mm‐diameter probe (Ayón‐Reyna and others ). The surface of the bottom of each stem was penetrated (5 mm depth) with a constant speed of 50 mm/min (Marangoni and others ).…”
Section: Methodsmentioning
confidence: 99%
“…A Minolta colorimeter (model CR‐200; Minolta Co. Ltd., Osaka, Japan) was used to measure color at the center of the stem according to Ayón‐Reyna and others () based on the CIELAB color parameters L *, a *, and b *. Total color difference (Δ E ) was calculated using the equation: ΔE=[]()L*Lf*2+()a*af*2+()b*bf*21/0pt122where L f *, a f *, b f * and L *, a *, b *are color parameters for fresh and after treatment samples, respectively.…”
Section: Methodsmentioning
confidence: 99%